THE INTEGRATION OF JOYFULL LEARNING WITH FLIPPED CLASSROOM-BASED APPLICATIONS - Rindaningsih, Ida (Journal of Higher Education and Academic Advancement, 2024)
Objective: This study aims to examine the relationship between the Joyful Learning approach and the application of Flipped Classroom-based applications to student engagement and learning outcomes at the elementary school level. The problems raised focus on the effectiveness of the integration of the two innovative approaches in improving the quality of learning and academic achievement of students. Method: This study uses a quantitative approach with a correlational design. The sample consisted of 60 grade V students from an elementary school in Sidoarjo who had implemented digital application-based learning. The instruments used include a Likert scale-based questionnaire to measure students' perception of Joyful Learning and Flipped Classroom, as well as learning outcome tests to assess academic achievement. Data analysis was performed using descriptive statistics, Pearson correlation, and multiple linear regression. Results: The results showed that although the average score of the implementation of Joyful Learning and Flipped Classroom was relatively high, no statistically significant effect was found on student learning outcomes (p > 0.05). The correlation between the independent variable and the dependent variable shows a positive but weak relationship. The hypothesis proposed in this study is not empirically proven. Novelty: These findings suggest that the success of the integration of Joyful Learning and Flipped Classroom is heavily influenced by factors beyond the learning model itself. This research contributes to the development of more contextual digital learning strategies and suggests the need for a more holistic approach to improve student engagement and learning outcomes. Follow-up research is recommended to examine mediating and moderator variables that can strengthen the relationship between innovative learning methods and academic achievement